The effects of ROS in prostatic stromal cells under hypoxic environment. (June 2015) - Ren, Hailin; Li, Xiaona; Cheng, Guojun; Li, Ning; Hou, Zhi; Suo, Jiming; Wang, Jian; Za, Xi
Abstract Objective: The objective of this study is to explore the effects of reactive oxygen species (ROS) under hypoxic environment in prostatic stromal cells (PSC). Methods and materials: To detect the expression of ROS in PSC and the tissues of benign prostatic hyperplasia (BPH) by flow cytometry; under hypoxic conditions, to observe the changes of cells growth and ROS in PSC; quantitative PCR was used to detect hypoxia inducible factor-1α (HIF-1α), androgen receptors (AR), vascular endothelial growth factor (VEGF), and interleukin-8 (IL-8) in PSC; After edaravone intervening, to examine the changes of cells growth, ROS, HIF-1α, AR, VEGF, and IL-8 under hypoxic conditions. Results: The expression of ROS in tissues and cells which under hypoxic condition was significantly increased. 3% O2 promoted the proliferation. The HIF-1α, AR, VEGF, and IL-8 were upregulated under 3% O2. After edaravone intervening, ROS significantly decreased, HIF-1α and VEGF were downregulated, and cell proliferation declined. Conclusions: Hypoxia stimulates the generation of ROS, and the ROS may play a key role in BPH.